Evaluación de los factores de conducción eficiente en vehículos particulares y su relación con la carga contaminante proveniente del consumo de combustible (2021)
The purpose of this document is to explain the associated factors that affect fuel consumption due to the habitual behaviors and driving styles exhibited by drivers in their vehicles; it also explains the mobility factors that atrophy vehicle traffic in cities and that also directly influence fuel consumption. To complement, this work aims to publicize driving aspects that can be improved, in order to optimize the vehicle's fuel as much as possible and inform some technologies that are currently being used to alleviate traffic in cities, as well as some global change initiatives that vehicles companies and districts are implementing or intend to do in the future.